Pengaruh Career Expectation, Work-Family Balance, Motivation, Incomes Terhadap Career advancement dengan Organizational Commitment Sebagai Variabel Intervening - Putri Anggraini; Sumitro Sarkum; Novrihan Leily Nasution (Akuntansi & Ekonomika, 2021)
Career progress of an employee is the result or work performance of employees who are assessed in terms of quality and quantity based on work standards determined by the organization. Optimal performance, namely performance that meets organizational standards and supports the achievement of organizational goals. In collecting this data using Accidental Sampling, which means that the sampling method involves random employees as the research sample. Using the Slovin formula with an error rate of 5%, The research sample totaled 399 respondents. Respondents in this study were employees who were in South Labuhanbatu Regency using Google Forms which the authors would later distribute on social media such as Facebook, WhatsApp and other social media.